Revascularization of a Previously Treated Mandibular First Molar with Open Apices: A Case Report - Feli , Mojgan; Taheri , Anita; Mehrabani, Mahgol (Iranian Endodontic Journal, 2024)
In this case report, the regeneration method was used to treat the previously treated first molar, which presented with symptoms of pain during chewing and secondary acute apical periodontitis. Due to the importance of preserving the patient’s permanent teeth in order to maintain optimal space and function, the regeneration treatment was performed in two visits and according to the American Association of Endodontists (AAE) guidelines. The continuation of tooth root development, healing of periapical radiolucency and positive response to sensibility test (cold test) were observed during follow-up radiographs at intervals of 6 months, 1 year & 2 year.